Prevalence and severity of dyspepsia in Saudi Arabia: A survey-based study - Abdulrahman Alwhaibi; Sultan Alghadeer; Salmeen Bablghaith; Syed Wajid; Ziyad Alrabiah; Abdulaziz Alhossan; Mohammed Al-Arifi (Elsevier, 2020)
Background and aim: Dyspepsia is one of the gastrointestinal diseases that is very common worldwide. Despite its prevalence globally, which ranges between 1.8% and 57%, no study has assessed the prevalence in Saudi Arabia. This study was aimed to investigate the prevalence and severity of dyspepsia in the general population of Saudi Arabia. Methods: A modified Short-Form Leeds Dyspepsia Questionnaire (SF-LDQ) was utilized to conduct our study. The questionnaire score ranges between 0 and 32, where zero indicated no dyspepsia, a score of 1-8 indicated mild dyspepsia, a score of 9-15 indicated moderate dyspepsia and a score of higher than 15 represented severe dyspepsia. Socio-demographic data of the participants including age, gender, marital status, BMI, job description, insurance, and education level were collected. Using Statistical Package for Social Sciences version 21.0 (SPSS), a univariate analysis was performed to assess the association of participants characteristics with the prevalence of dyspepsia, whereas logistic regression analysis was used to correlate their characteristics with the severity of dyspepsia. Results: During a period of one month, March 1st to 31st 2019, a total of 778 participants have completed the survey. Most of them were females accounting for 68% of the population, married (63.9%), middle aged (range 34-51 years old) and literate with high school education (72.3%). Ninety two percent (92%) of the study population were found to experience dyspepsia. However, there is no significant association between socio-demographic characteristics and dyspepsia or its severity as well. Conclusion: The prevalence of dyspepsia in Saudi Arabia is the highest in the gulf region which would potentially lead to more GI complications, and associate to poor health and economic outcomes. Education programs are essential to raise the people awareness of dyspepsia and the appropriate ways to prevent it.